(untitled) (ENTHYMEMA, 2013)
There is a particular space-time combination in which poetry is meant to find its perfect place, its perfect happening: it’s the meridian moment, the midday spent in a locus amoenus singing and playing along with fellow-poets. It seems to be what Bachtin defines as a cronotope. Anyway, in lyric poetry this time-space reveals itself to be more and more a foundational ideal. In the bucolic world a man has to renounce personal experience, because it is a place full of (re-told) stories but without Story. Lyric poetry, instead, needs existential experience. Even bucolic love is not suffered by the subject as much as elegiac love, it does not possess the same degree of reality. The bucolic midday could be desired and invoked as a utopia of eternal harmony, but it cannot be real in a lyric text. Even when the (young) subject finds himself in the middle of such locus amoenus – as Freud shows in his story – he has to reject the full situational enjoyment and think that behind all that vital splendour there is always the constant menace of time and death. The subject defines himself in the desiring position and he is too attracted and tied to the object to abandon it and turn his mind toward abstraction as a true philosopher would (platonically) do. Finally, the investigation of the topos will lead to a reconsideration of Lacan’s idea of artistic creativity as a sublimation.